A 48 year old postmenopausal woman with dull aching lower abdominal pain and heaviness in the abdomen (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below:A 48 year old postmenopausal lady, para-6 (alive) came to the outpatient department as a diagnosed case of ovarian tumor with history of incomplete surgery. The patient was reasonably well two years back, then she developed dull aching lower abdominal pain and heaviness in abdomen. For that reason, she went to a local doctor and diagnosed as a case of ovarian tumor by ultrasonography. She had laparotomy on 22 May 2016 at Mymensingh private clinic but the tumor was not removed completely due to extensive adhesion. Few tissues were taken and sent for histopathology and found fibroma of ovary.